Insurance literacy: Significance of its dimensions for insurance inclusion in Uganda - Archillies Kiwanuka; Athenia Bongani Sibindi (Economies, 2023)
The aim of the study was to establish the significance of the individual components of insurance literacy - knowledge, skills, attitude and behaviour - in explaining insurance inclusion in Uganda. The study was correlational and cross-sectional by design. Hence, 400 responses were obtained from individuals who enrolled for insurance. A hierarchical multiple regression analysis was adopted to test the predictive power of the dimensions of insurance literacy on insurance inclusion in Uganda. Before performing correlational and regression analyses, the study variables were tested for parametric assumptions, convergent and discriminant validity, common method variance and exploratory factors. The results of the study revealed that knowledge, skills and attitude significantly and positively predicted insurance inclusion in Uganda. Contrary to prior studies, behaviour was found to have an insignificant positive influence on insurance inclusion in Uganda. Overall, the individual components of insurance literacy explained 38.5% of the variation in insurance inclusion in Uganda. Notably, the current study contributes to the nascent literature on insurance literacy and insurance inclusion. Earlier studies have ignored the insurance component of financial inclusion. The originality of this study lies in that it is the first to examine the significance of the individual dimensions of insurance literacy towards explaining insurance inclusion. The implication of this study is that policymakers should consider insurance literacy in national financial inclusion strategies and financial literacy programmes in order to foster insurance inclusion.
Keywords: 330; attitude and behaviour; financial inclusion; financial literacy; insurance inclusion; insurance knowledge; insurance literacy; skills; Uganda